2018
DOI: 10.1017/s0022377818001162
|View full text |Cite
|
Sign up to set email alerts
|

On annihilation of the relativistic electron vortex pair in collisionless plasmas

Abstract: In contrast to hydrodynamic vortices, vortices in a plasma contain an electric current circulating around the centre of the vortex, which generates a magnetic field localized inside. Using computer simulations, we demonstrate that the magnetic field associated with the vortex gives rise to a mechanism of dissipation of the vortex pair in a collisionless plasma, leading to fast annihilation of the magnetic field with its energy transforming into the energy of fast electrons, secondary vortices and plasma waves.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…An experimental study by Yabuuchi et al (2009) confirms anomalous dissipation of energy in electron current structures passing through an inhomogeneous plasma as predicted by Yadav et al (2009). With the inclusion of ion dynamics particle-in-cell studies have revealed the explosion of these structures at ion time scales (Lezhnin et al 2016).…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…An experimental study by Yabuuchi et al (2009) confirms anomalous dissipation of energy in electron current structures passing through an inhomogeneous plasma as predicted by Yadav et al (2009). With the inclusion of ion dynamics particle-in-cell studies have revealed the explosion of these structures at ion time scales (Lezhnin et al 2016).…”
Section: Introductionsupporting
confidence: 52%
“…Their dynamics has been described by several authors (Bulanov et al 1997; Das 1999) with the help of fluid simulations of EMHD and its generalizations (Yadav, Das & Kaw 2008; Yadav et al 2009; Yadav 2011). Particle-in-cell simulations studying the properties of the electron vortex current have also been carried out, even as late as in 2018 by Lezhnin et al (2018), showing the annihilation of the magnetic field in a collisionless inhomogeneous plasma. An experimental study by Yabuuchi et al (2009) confirms anomalous dissipation of energy in electron current structures passing through an inhomogeneous plasma as predicted by Yadav et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the relativistic laser plasma the generated magnetic field plays an active role leading to the magnetic interaction and coalescence of the self focusing channels, their bending, and accumulating of the magnetic energy [120,121] . The magnetic field left behind the ultrashort laser pulse as well as at the vacuum plasma interface has a pattern determined by the electron vortices [122] , which can annihilate [123] resulting in the electron and ion acceleration [124,125] .…”
Section: Discussionmentioning
confidence: 99%
“…Along with the recent rapid development of intense laser technology 1,2 , such kind of structures can be generated and studied in detail in intense laser plasma interactions. Among them electron vortices formed in relativistic laser plasmas have recently aroused broad interests [3][4][5][6][7][8] due to their wide presence in nature and potential applications in the laser electron and ion acceleration [9][10][11][12][13][14][15][16][17][18][19][20][21] , as well as extremely strong magnetic field generation 22,23 . Compared with normal target sheath field in laser solid interaction, in addition to ion acceleration, the vortex field can also be used to collimate the accelerated ions 11 , and gena) minchen@sjtu.edu.cn b) Sergei.Bulanov@eli-beams.eu erate quasi-monoenergetic protons with energy of hundreds of MeV 21 .…”
Section: Introductionmentioning
confidence: 99%